Sustainable ophthalmology: an overview of concepts and practices - Maheshwari, Anjali; Dave, Vivek Pravin; March de Ribot, Francesc; Romano, Mario R; Arevalo, J Fernando; Özdek, Şengül; Chang, Andrew; Ruamviboonsuk, Paisan; Pappuru, Rajeev Reddy; Fernandes, Merle; Das, Taraprasad (Eye (London), 2025)
Climate change and global warming are significant global challenges, with healthcare systems contributing substantially to greenhouse gas (GHG) emissions. (1) This review examines the environmental impact of ophthalmic care, focusing on energy consumption, surgical waste, single-use supplies, and patient travel. Strategies to reduce the carbon footprint include adopting telemedicine, digital records, energy-efficient infrastructure, and sustainable surgical practices like reusing instruments, recycling, and minimising waste. Decentralising eye care and increasing the proximity of services to people and the community, for example, doorstep healthcare, can further lower travel-related emissions. Sustainability also aligns with financial efficiency, particularly in resource-limited settings where affordability is critical. Collaborative efforts among policymakers, industry, and clinicians are vital to fostering environmentally conscious ophthalmic care. This article highlights actionable strategies to integrate environmental responsibility into ophthalmology, balancing quality care, cost efficiency, and sustainability for a greener future in healthcare.